Symbiotic housing model for low-income affordable housing in densely-populated urban centres by non-profit housing developers in Nigeria - Habibullah, Muhammadu Kyari (2020)
The challenges facing low-income workers in many developing countries classified as urban poor in providing affordable housing are the result of insufficient housing policies being enforced. Such commitments have been left without fulfilment, with numerous housing policies from these nations, including Nigeria. Housing issues in these countries have thus increased, citing Nigeria as a case, due to certain fundamental factors that hinder the successful implementation of policies. As a result, governments are facing tremendous pressure on demand for affordable housing, particularly the low-income groups. Over the years, the provision of affordable housing for low-income earners in Abuja, Nigeria's new federal capital, has been shown to be ineffective; this problem is particularly evident from the poor living standards among low-income groups in the densely populated urban areas within the federal capital territory. Though, in Nigeria the main sources of housing finance are Government-by given housing loans to staff, grants to the Federal Housing Authority. The mortgage instruments in operation are cumbersome there by making accessibility to fund by interested borrowers almost impossible. With the current NHP 2002 observed that the main problem of availability of land for housing in Nigeria is that of accessibility, ownership and use. The chronic difficulties in making urban land easily accessible to potential developers have entrenched systemic urban land speculation, which often drives up land prices beyond the reach of an average household. The role of land use planning system in housing development is not only to meet housing needs, but to also encourage the efficiency of the housing market system. However, from previous literature by scholars it is understood that past and present governments have been and are still implementing some kind of affordable housing delivery programs, they have not been able to address the needs of income groups for housings demands. In addition, the performance of the housing stock is also subject to intense scrutiny with regard to norm, adequacy and social interactions and lowincome affordable housing were not properly addressed. Thus, this research proposes for a symbiotic affordable housing model that could improve the permanent affordable housing supply for low income group in densely populated urban centres in Nigeria by Non-Profit Housing Developers. The study adapts a qualitative single holistic case study research methodology to explain the underperformances in affordable housing in the municipal area council. It further looks at housing provision in Malaysia, USA, UK, Japan, China, and Singapore with strategies used in achieving the programs, and draws a link with the Nigerian situation. This could also inform stakeholders operating in the public housing sector, especially in the federal capital development authority (FCDA) Abuja Nigeria.